Religion or belief, discrimination and equality: Britain in global contexts - Weller, P; Purdam, K; Ghanea, N; Cheruvallil-Contractor, S (Bloomsbury Academic, 2013)
In recent years, controversial issues related to religion or belief, discrimination, equality and human rights have come to the fore, especially in the context of public debates around multiculturalism following the 'social policy shock' created by the impact of violent religious extremism. For example should there be restrictions on what people can wear in the work place based on their religious identity? Should religious organizations be exempt from aspects of equalities legislation which are not in line with their beliefs and values? How should non-religious identities be recognized?